Tuning the reduction and conductivity of solution-processed graphene oxide by intense pulsed light. (June 2016) - Al-Hamry, A.; Kang, H.; Sowade, E.; Dzhagan, V.; Rodriguez, R.D.; Müller, C.; Zahn, D.R.T.; Baumann, R.R.; Kanoun, O.
Abstract: We report about the reduction of spin-coated graphene oxide (GO) layers by intense pulsed light (IPL) treatment. The reduction is achieved in a few seconds resulting in semi-transparent graphene thin films with electrical conductivities up to 6.6 S/cm. In comparison to GO reduction by conventional thermal annealing in an oven, the IPL method is much faster, enabling applications in transparent and flexible polymer substrates. Moreover, this process is roll-to-roll compatible and chemicals-free. The parameters of IPL were optimized in order to tune the conductivity of reduced GO (rGO) films as a function of exposure energy, pulse duration, and number of pulses. The effect of IPL parameters on the morphology and the electrical properties of rGO films were investigated by vis-NIR, X-ray photoelectron, and Raman spectroscopies, as well as scanning electron microscopy, atomic force microscopy, and sheet resistance measurements. The correlation between Raman spectroscopy analysis and sheet resistance shows that the G band width can be used to evaluate the conductivity of the rGO. The IPL, in a time frame of seconds, results in higher conductivity than oven annealing of 30 min at 400 °C, which is also evidenced in the Raman spectra showing the same structural changes as X-ray photoelectron spectroscopy.